1992
DOI: 10.1002/pd.1970120404
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance in a prenatal screening programme for Down's syndrome incorporating serum‐free hCG subunit analyses

Abstract: A prenatal screening programme for Down's syndrome potentially detecting 76 per cent of affected pregnancies in the South Australian general population at an amniocentesis rate of 3.9 per cent was designed following analysis of mid-trimester serum samples from 57 women who carried an affected fetus. This equates to one affected pregnancy being detected for 41 chromosomal analyses performed. For the experimental series, 75.4 per cent of affected pregnancies were detected, while 4.1 per cent of control specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 24 publications
3
29
1
Order By: Relevance
“…Although the use of total hCG is unequivocally established in serum screening for Down's syndrome (Crossley et al, 1991;Haddow et al, 1992;Cheng et al, 1993), a superior detection rate was achieved in several studies by using free -hCG (Spencer, 1991;Ryall et al, 1992;Spencer et al, 1992a;Wald et al, 1993;Macri et al, 1994). Free -hCG has been suggested as the major contributor to the increased sensitivity of two-analyte screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of total hCG is unequivocally established in serum screening for Down's syndrome (Crossley et al, 1991;Haddow et al, 1992;Cheng et al, 1993), a superior detection rate was achieved in several studies by using free -hCG (Spencer, 1991;Ryall et al, 1992;Spencer et al, 1992a;Wald et al, 1993;Macri et al, 1994). Free -hCG has been suggested as the major contributor to the increased sensitivity of two-analyte screening.…”
Section: Discussionmentioning
confidence: 99%
“…Since the -subunit is specific to hCG, some authors advocate incorporating free -hCG in serum screening for Down's syndrome. Although a few authors are still uncertain of the effectiveness of using free -hCG in prenatal screening for Down's syndrome Wald et al, 1994), measurement of free -hCG has been reported to improve the performance of Down's syndrome screening (Ryall et al, 1992;Spencer et al, 1992a;Wald et al, 1993;Macri et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The most optimal cut-off risk for the screening was calculated to be 1 in 250 (Baumgarten, 1985). During the early 1990s, the triple test was adjusted by the replacement of hCG with the free beta subunit of hCG (fβ-hCG) (Macri et al, 1990, Ryall et al, 1992. Moreover, in 1996, inhibin-A was found to contribute to the current triple test (Wald et al, 1996) and with the addition of inhibin-A the 'quadruple test' was conceived.…”
Section: Prenatal Screening For Down Syndromementioning
confidence: 99%
“…This fact would support free ßhCG to be the more effective marker. On the other hand in all comparative studies standard deviations for hCG are often considerably smaller than for free ßhCG [2,4,[8][9][10]21] supporting total hCG. Tendencies of such opposite effects on discrimination could be observed by our study although the differences in means and standard deviations of hCG and free ßhCG were not as prominent as in other studies.…”
Section: Discussionmentioning
confidence: 99%